2000
DOI: 10.1364/ol.25.000566
|View full text |Cite
|
Sign up to set email alerts
|

Phase-only optical encryption

Abstract: We have implemented a phase-only optical encryption and decryption system with a readout based on the generalized phase-contrast method. The experimental system has been implemented with liquid-crystal spatial light modulators to generate binary phase-encrypted masks and a decrypting key. A phase-contrast filter is used to display the phase information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(60 citation statements)
references
References 15 publications
0
59
0
1
Order By: Relevance
“…The methods have been proved to be useful by numerical simulations. Phase-coding techniques have widely been used due to the suitability for optical encoding and decoding with high degree of security (Neto & Sheng, 1996, Javidi & Ahouzi, 1998, Towghi et al, 1999, Tan et al, 2000, and Mogensen &Gluckstad, 2000. However, they have some difficulties due to the lack of efficient optical devices used in the systems.…”
Section: Methods Of Phase-codingmentioning
confidence: 99%
“…The methods have been proved to be useful by numerical simulations. Phase-coding techniques have widely been used due to the suitability for optical encoding and decoding with high degree of security (Neto & Sheng, 1996, Javidi & Ahouzi, 1998, Towghi et al, 1999, Tan et al, 2000, and Mogensen &Gluckstad, 2000. However, they have some difficulties due to the lack of efficient optical devices used in the systems.…”
Section: Methods Of Phase-codingmentioning
confidence: 99%
“…Many techniques for the optical encryption of image data have been proposed and implemented in recent years [51][52][53][54][55][56][57][58][59][60][61][62]. Most perform encryption with a random phase mask positioned in the input, Fresnel, or Fraunhofer domain, or a combination of domains.…”
Section: Optical Image Encryptionmentioning
confidence: 99%
“…In recent years there have been a number of proposed attacks [92][93][94][95][96][97] on DRPE-type encryption systems, including those systems that operate exclusively with phase [98,99]. Many of these attacks have shown that by only approximating the key one can get adequate decryption of encrypted images.…”
Section: Optical Image Encryptionmentioning
confidence: 99%
“…5(a)] than the SOM. The resulting NRMS reconstruction errors [calculated using (5)] for various numbers of clusters are compared in Fig. 8.…”
Section: Evaluation Of Nonuniform Quantizationmentioning
confidence: 99%